Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 34 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Odorrana khalam (Stuart, Orlov & Chan-ard, 2005)", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 34 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0024207-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences